استقلالية البنك المركزي وتأثرها بالمالية العامة - محمد حياة جمعة (lark, 2019)
Abstract The study showed that the public finances have an impact on the work of the Central Bank and its independence through a number of monetary variables such as inflation, which affect the public finances through expenditure and revenue on inflation, for example when the consumption expenditure is greater than investment expenditure in this case will lead public finances through one of its tools To raise inflation rates. As well as in the auction of currency is noted in the rent countries are oil revenues constitute a large proportion of the state budget and controlled by the Ministry of Finance (the government) which controls the foreign currency (dollar) and sells to the Central Bank of the local currency and the proportion of sales and purchases of currency steady because it is affected by oil revenues In turn vulnerable to fluctuations in global oil prices